Soil physicochemical and ethnobiological studies on the peat swamp forests of Southern Papua, Indonesia - AKHMAD KADIR; ROSYE H.R. TANJUNG; SUHARNO SUHARNO; BASA T. RUMAHORBO; MUHAMMAD A. REZA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kadir A, Tanjung RHR, Suharno, Rumahorbo BT, Reza MA. 2020. Soil physicochemical and ethnobiological studies on the peat swamp forests of Southern Papua, Indonesia. Biodiversitas 21: xxxx.  Peatlands play an important role in human life, particularly its direct impact for the locals. People in peatlands depend on the availability of natural resources, including in Papua. The purpose of this research was to determine the important role of peatland areas in the lives of locals in southern Papua. The survey was conducted using the purposive sampling method. Peat soil samples were analyzed at the Balai Penelitian dan Teknologi Pertanian (Agricultural Research and Technology Center) (BPTP) Yogyakarta. The results showed that peatlands in the southern part of Papua, specifically Mappi District, belong to the fibric peats category. Soil analysis results showed that the average pH is 4.04 (acidic), organic C is 16.39% (high), total N is 1.12% (very high), and C/N ratio is 14.69(moderate). In general, the local’s knowledge about peat swamp is still low (26.98%), most of them (73.02%) do not know the existence of peat swamp forest. So far, people only know the forest as swamp forest. The locals still depend on forest areas to fulfill their daily needs, therefore peat areas land-use must be followed by wise management so that they can be made sustainable.